The impact of Lacticaseibacillus paracasei GMNL-143 toothpaste on gingivitis and oral microbiota in adults: a randomized, double-blind, crossover, placebo-controlled trial - Min-Kang Lee; I-Hui Chen; I-Ling Hsu; Wan-Hua Tsai; Tzong-Yi Lee; Jhih-Hua Jhong; Bai-Chia Liu; Tsui-Yin Huang; Fang-Kuei Lin; Wen-Wei Chang; Ju-Hui Wu (BMC Oral Health, 2024)
Abstract Background This study examines the oral health benefits of heat-killed Lacticaseibacillus paracasei GMNL-143, particularly its potential in oral microbiota alterations and gingivitis improvement. Methods We assessed GMNL-143’s in vitro interactions with oral pathogens and its ability to prevent pathogen adherence to gingival cells. A randomized, double-blind, crossover clinical trial was performed on gingivitis patients using GMNL-143 toothpaste or placebo for four weeks, followed by a crossover after a washout. Results GMNL-143 showed coaggregation with oral pathogens in vitro, linked to its surface layer protein. In patients, GMNL-143 toothpaste lowered the gingival index and reduced Streptococcus mutans in crevicular fluid. A positive relationship was found between Aggregatibacter actinomycetemcomitans and gingival index changes, and a negative one between Campylobacter and gingival index changes in plaque. Conclusion GMNL-143 toothpaste may shift oral bacterial composition towards a healthier state, suggesting its potential in managing mild to moderate gingivitis. Trial registration ID NCT04190485 ( https://clinicaltrials.gov/ ); 09/12/2019, retrospective registration.